Farmers’ Aspirations, Happiness, and Sugarcane Production in the Visayas, Philippines - Oñal, Jr., Paulino A.; Andrade, Francis E; Oñal, Paulino Miguel M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Aspirations are long-term ambitions in one’s life.  Farmers aspire to achieve happiness in their faming activities. Happy farmers are satisfied individual that can easily increase their sugarcane production. The study aims to measure the aspirations of the farmers and its correlation to the level of the production of sugarcane crop in the Philippines. Descriptive method was employed in the study. The instrument used was the validated survey questionnaire used by the group of Oñal on their study in 2021. The 320 sugarcane farmers were randomly identified at the seven locations in the Visayas area of the Philippines.  Analysis of Variance (ANOVA) shows that there’s a significant difference in the production of sugarcane among location with an average of 50-64 Tons Cane per hectare (TC/ha) (alpha = 0.05). Furthermore, a significant differences in terms of farmers emotional well-being (happy farmers) indicates a high production of >65 TC/ha (alpha = 0.05). Relatively, the degree of farmers’ happiness have weak to moderate correlation with sugarcane production (alpha = 0.01). Considering that farmers degree of happiness indicates a weak to moderate correlation with productivity, interventions that enhance farmers’ well-being such as; stable pricing, affordable credit, and efficient milling may indirectly contribute to improved yields.